Variation in the holm oak leaf proteome at different plant developmental stages, between provenances and in response to drought stress. - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Jorrín, Jesús (Proteomics, 2006)
Major proteins of the holm oak leaf proteome have been previously identified using a combination of 2-DE, MS analysis and BLAST similarity search (Jorge et al., Proteomics 2005, 5, 222-234). That study, conducted with field samples from mature trees, revealed the existence of a great variability in the 2-DE protein map, with qualitative as well as quantitative changes, both analytical and biological. A similar study has been carried out with 2-year-old seedlings to analyze and study: (i) changes in the 2-DE protein profile at different tree developmental stages; (ii) the 2-DE protein map variability between three different Spanish provenances; and (iii) variations in the 2-DE protein profile in response to drought stress. Although the protein profile of leaves from seedlings and mature trees was fairly similar, the biological variance found was lower in the former. In the present study, new proteins have been identified. At least four different protein spots differentiated Spanish provenances, two of them identified as an ATP synthase alpha chain, and a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase. Fourteen different protein spots were qualitatively variable between well-watered and drought-stressed seedlings, with some of them corresponding to enzymes of carbohydrate and protein metabolism. Data presented indicated the mobilization of storage proteins and carbohydrates, as well as photosynthesis inhibition under drought conditions.
Keywords: Dehydration; Dehydration: metabolism; Disasters; Electrophoresis, Gel, Two-Dimensional; Plant Leaves; Plant Leaves: metabolism; Proteome; Proteome: metabolism; Proteomics; Quercus; Quercus: embryology; Quercus: metabolism; Seedling; Seedling: metabolism

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S.; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C. (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
The following values have no corresponding Zotero field: accession-num: 15346811
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure

Cryopreservation of Quercus suber and Quercus ilex embryonic axes: in vitro culture, desiccation and cooling factors. - Gonzalez-Benito, M Elena; Prieto, Roberto-Moreno; Herradon, Esther; Martin, Carmen (Cryo letters, 2002)
This study examines different factors included in the cryopreservation protocols for Quercus ilex and Q. suber embryonic axes. In vitro incubation temperature played an important role in the appropriate development of Q. ilex axes, as 15 degrees C was superior to 25 degrees C. Q. suber axes proved to be more sensitive to desiccation and cooling. Poor survival (35%) was observed when axes were included into cryovials and then in liquid nitrogen, and none when immersed in sub-cooled liquid nitrogen (-210 degrees C). Q. ilex axes showed poorly organised development in vitro (c. 50% of non-cooled axes showed shoot development). However, c. 80% survival was observed after cryopreservation (either in liquid nitrogen or sub-cooled liquid nitrogen at 0.34 g water / g dry weight), of which c. 15% showed shoot development.
Keywords: Cryopreservation; Cryopreservation: methods; Cryoprotective Agents; Cryoprotective Agents: pharmacology; Culture Techniques; Culture Techniques: methods; Desiccation; Desiccation: methods; embryonic axes; germination; germination temperature; Germination: drug effects; liquid nitrogen; plantlet development; Quercus; Quercus: embryology; Seeds; Seeds: chemistry; Seeds: embryology; Survival Rate; Temperature; water; Water: analysis